Factors Influencing Depression in Adolescents Focusing on the Degree of Appearance Stress - Mihye Lim; Myoungjin Kwon (MDPI AG, 2023)
This descriptive cross-sectional study examined the factors that affect depression in adolescents focusing on how stressed they are regarding their appearance (hereafter, degree of appearance stress). Data from 6493 adolescents from the 2020 Korean Youth Risk Behavior Survey were used. Using SPSS 25.0, a complex sample plan file was created, weighted, and analyzed. The frequency, chi-square test, independent t-test, and linear regression were used for the complex sample analysis. The results showed that among adolescents with low appearance stress, depression was significantly affected by the number of breakfast meals, weight control efforts, smoking, loneliness, subjective physical appearance, and smartphone overdependence. Among those with high appearance stress, depression was significantly affected by academic grades, weight control efforts, drinking habits, loneliness, subjective physical appearance, and smartphone overdependence. Furthermore, these factors differed according to the degree of appearance stress. Thus, while developing interventions for mitigating depression in adolescents, the degree of appearance stress should be considered, and a differentiated strategy should be used accordingly.